A Comparative Analysis of China’s New Era Economic Diplomacy and the Economic Diplomacy Strategy of the Biden Administration - Huang, Jiali (Journal of Modern Social Sciences, 2025)
Against the backdrop of intensifying Sino-US strategic competition, the Biden administration’s economic diplomacy exhibits a pronounced inclination toward exclusive minilateralism. At the global level, it advocates the Partnership for Global Infrastructure and Investment (PGII), while at the regional level, it establishes the Indo-Pacific Economic Framework (IPEF) to collectively counter China’s developmental advantages and form exclusive, targeted economic alliances. In contrast, China’s economic diplomacy in the new era is guided by the principles of inclusivity and open multilateralism. Globally, it actively promotes the concept of a community with a shared future for mankind and the Global Development Initiative (GDI), fostering inclusive and equitable development across nations. Concurrently, China continues to expand the Belt and Road Initiative (BRI), transforming it from a regional cooperation platform into a globally recognized public good that facilitates pragmatic development. A comparative analysis of the economic diplomacy approaches of the two countries facilitates a clearer understanding of the divergent pathways of Sino-US economic development and external cooperation under complex geopolitical conditions, while also providing insights into the evolving trajectory of their economic diplomacy amid great power competition.